2021
DOI: 10.3390/en14041031
|View full text |Cite
|
Sign up to set email alerts
|

State of Art of Alkaline Earth Metal Oxides Catalysts Used in the Transesterification of Oils for Biodiesel Production

Abstract: Biodiesel produced through catalytic transesterification of triglycerides from edible and non-edible oils and alcohol is considered an alternative to traditional petro-diesel. The interest in the use of alkaline earth metal oxides as heterogeneous basic catalysts has increased due to their availability, non-toxicity, the capacity to be reused, low cost, and high concentration of surface basic sites that provide the activity. This work is a compilation of the strategies to understand the effect of the source, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 132 publications
0
25
0
Order By: Relevance
“…To evolve the metalorganic composites as good platforms for various applications, alkaline metal oxides have been well purposed as organic linkers with metal-organic composites because of their excellent structural, catalytic, and antimicrobial activities. The alkaline earth metal oxides working for the various chemical reaction and transesterification reaction survey the mandate of their activity:-BaO, AgO, CaO, SrO, MgO; …etc [16][17][18][19]. Unique metal oxides either establish low activity and/or leaked out into the reaction combination to cause the uniform contribution in the catalytic activity [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To evolve the metalorganic composites as good platforms for various applications, alkaline metal oxides have been well purposed as organic linkers with metal-organic composites because of their excellent structural, catalytic, and antimicrobial activities. The alkaline earth metal oxides working for the various chemical reaction and transesterification reaction survey the mandate of their activity:-BaO, AgO, CaO, SrO, MgO; …etc [16][17][18][19]. Unique metal oxides either establish low activity and/or leaked out into the reaction combination to cause the uniform contribution in the catalytic activity [16].…”
Section: Introductionmentioning
confidence: 99%
“…The alkaline earth metal oxides working for the various chemical reaction and transesterification reaction survey the mandate of their activity:-BaO, AgO, CaO, SrO, MgO; …etc [16][17][18][19]. Unique metal oxides either establish low activity and/or leaked out into the reaction combination to cause the uniform contribution in the catalytic activity [16]. To improve both the reactivity well as stability, mixed metal oxides of various alkali earth Egyptian Journal of Chemistry http://ejchem.journals.ekb.eg/ ________________________________________________ Egypt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For RME, we found mainly alkali and alkaline earth metals showing the highest abundance compared to the elemental composition of PM 0.25 of B0 and GTL. The higher concentrations of alkali and alkaline earth metals in the PM of RME could be explained by their expected occurrence in natural sources such as rapeseed oil and by their common use as catalysts in the transesterification process of biofuels (Arzamendi et al 2008;Mohadesi et al 2014;Tavizón-Pozos et al 2021) (Arzamendi et al 2008). Recently, Tavizón-Pozos et al concluded that the combined use of alkaline earth oxides with alkaline metals might enhance their basicity so that more active sites would be available and a higher resistance to environmental factors could be achieved (Tavizón-Pozos et al 2021).…”
Section: Insert)mentioning
confidence: 99%
“…Alkaline earth metals oxides such as Mg, Ba, Sr, Ca and Be, have been used for the production of biodiesel via the transesterification process [68].…”
Section: Alkaline Earth Metal Oxidesmentioning
confidence: 99%